USING FLASH EXPRESSIONS BOOK AS INSTRUCTIONAL MEDIA TO VOCABULARY MASTERY IN LEARNING ENGLISH - Loi, Oktaria Putri; Tamba, Sri Blesiski; Pangaribuan, Martauli; Saragih, Erikson (Universitas Pendidikan Ganesha, 2020)
The purpose to be reached in conducting this study is to share information about the use of flash expressions book as instructional media to enrich vocabulary mastery in learning teaching. It is true to say that there are lots of instructional media in such a way that they can be used to deliver the materials and to understand materials. According to certain research findings done by the students of the English Department at the University of Prima Indonesia, it is suggested to use the flash expressions book as instructional media to improve the quality of learning English. Because the flash expressions book has interesting materials and can provide learning motivation for readers, the flash expressions book has 4 main topics and more than 200 expressions that will help us to speak of expressions and canÂ enrich our vocabulary. Based on the information above, it is clear that the use of flash expressions book can be expected to be the solution to solve the problems thatÂ occurred in attempts to increase vocabulary mastery when learning English. The flash expressions book can be an excellent media to be used because it has many interesting expressions, easy to understand vocabulary, modern and simple